Assessment of the H2 Followed by Air Sintering of Co-doped In2O3 Based Diluted Magnetic Semiconductors - Rana Mukherji; Vishal Mathur; Arvind Samariya; Manishita Mukherji (Журнал нано- та електронної фізики)
The study shows the influence of Co doping, sintering in hydrogen atmosphere and re-heating on magnetic properties of In2O3.The In0.97Co0.03O samples were prepared by solid state reaction method. XRD patterns shows that Co ions take position of at the In3+ sites. The investigations at room temperature (RT) concludes that the Co doped In2O3 sample had achieved overlapped paramagnetic (PM) properties conquering the diamagnetic (DM) properties of In2O3. Additionally, it was found that the ferromagnetism (FM) is noticeably induced via H2-annealing at 300 K. This study also depicts that the sample is finally reverted to the PM state after further long sintering.